MANAGEMENT MODEL OF ILLEGAL LOGGING CONFISCATED GOODS AT RUPBASAN INSTITUTIONS IN THE PROVINCE - Subaidi, Joelman; Syahputra, Dedy; Jafar, Sofyan (RADJA PUBLIKA, 2022)
Management of confiscated illegal logging goods in general has been regulated by the Decree of the Director General of Corrections Number E2.UM.01.06 of 1986, and has been completed by Decree of the Director General of Corrections Number E1.35.PK.03.10 of 2002 concerning Implementation Guidelines and Technical Instructions for the Management of Confiscated Objects The State and the State's Loot in Rupbasan. The same thing is also regulated in Article 44 of the Criminal Code which states